2016
DOI: 10.1007/s11205-016-1326-1
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Income Replacement Profile Among EPF Retiree in Malaysia

Abstract: Social security policies often focus on replacement rates, which indicate retirement income or social security benefits in relation to preretirement income. The higher replacement rate among the pensioners would ensure that the ageing society would have sufficient income to lead a normal life after retirement. This study examined factors that influencing the income replacement rate of Malaysian Employee Provident Fund (EPF) retirees. The analysis was based on a nationwide survey conducted in 2013-2014 among EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…This causes the savings to grow at a very slow rate despite the country having one of the world's highest contribution rates for retirement savings. The issue of low wages among EPF members that led to low savings was well described in a previous study by Vaghefi et al (2017).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This causes the savings to grow at a very slow rate despite the country having one of the world's highest contribution rates for retirement savings. The issue of low wages among EPF members that led to low savings was well described in a previous study by Vaghefi et al (2017).…”
Section: Discussionmentioning
confidence: 65%
“…al, 2010;Argento et al, 2015;Ghilarducci et al, 2019 andBateman et al, 2023). Although there are studies conducted in Malaysia on early withdrawal from EPF retirement savings (Narayanan, 2002;Vaghefi et. al, 2017;Awang et al, 2020 andJaafar et al, 2021), there is still a lack of studies conducted on this topic in the event of a catastrophe.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth and lastly, considering the issue of policy or program implemented to eradicate old-age poverty, there are viable issues and challenges encountered and need future adjustment. For instance, the government needs to expand the scope of its policy recipients (Muis et al, 2020), improved the provision of health services in aging rural communities (Utomo et al, 2018;Mohd et al, 2014), strengthen rural-rural connections (Mohd et al, 2014), integrated social protection strategies must take into account the formal and informal support (Ismail et al, 2015), the government needs to review the old age assistant program (Vaghefi et al, 2016) and also raising the retirement age (Vaghefi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The retirement savings is expected to be exhausted within 3 years upon reaching retirement age (Principal, 2021)). Previous studies also reported that retirees with EPF face a higher risk of having a lower replacement rate during retirement years compared to retirees with a pension scheme (Vaghefi et. al., 2017).…”
Section: Employer Factorsmentioning
confidence: 91%